1990
DOI: 10.1007/bf00187337
|View full text |Cite
|
Sign up to set email alerts
|

Prothoracic DUM neurons of the cricket Gryllus bimaculatus ? responses to natural stimuli and activity in walking behavior

Abstract: Responses to sensory stimuli and spike activity during walking were investigated in bilaterally symmetrical dorsal unpaired median (DUM) neurons of the cricket. Intracellular recordings within the prothoracic ganglion were made either in restrained animals or in stationary walking specimens whilst parameters of their intended locomotion were measured. Three types of DUM cells were distinguished morphologically and physiologically. DUMa neurons send axons through segmental nerves. They often generated spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…11). This notion agrees with results in crickets (Gras et al, 1990), where a lesion of the neck connective tissues leads to a drastic reduction of the response to mechanosensory stimulation. Furthermore, the VUM neurons of the larvae of Manduca sexta receive descending inputs from the SEG (Johnston et al, 1997), which indicates that in different insect species mechanosensory information is first processed in the SEG and then is passed to modulatory unpaired median neurons.…”
Section: Efferent Thoracic Dum Neurons Can Be Divided In Subpopulatiosupporting
confidence: 86%
See 1 more Smart Citation
“…11). This notion agrees with results in crickets (Gras et al, 1990), where a lesion of the neck connective tissues leads to a drastic reduction of the response to mechanosensory stimulation. Furthermore, the VUM neurons of the larvae of Manduca sexta receive descending inputs from the SEG (Johnston et al, 1997), which indicates that in different insect species mechanosensory information is first processed in the SEG and then is passed to modulatory unpaired median neurons.…”
Section: Efferent Thoracic Dum Neurons Can Be Divided In Subpopulatiosupporting
confidence: 86%
“…The intersegmental coordination of the activity of DUM5 and DUM3,4,5 neurons is probably mediated by ascending and descending interneurons because lesions of both the abdominal and the anterior connective tissues led to an irreversible reduction in the number of common PSPs in these neurons. Gras et al (1990) observed a persistent reduction of PSPs in prothoracic DUM neurons when cutting the neck connectives in Gryllus bimaculatus. Furthermore, common intersegmental inputs have been shown in locust abdominal DUM neurons (Pflü ger and Watson, 1995) and in abdominal VUM neurons in Manduca sexta (Pflü ger et al, 1993).…”
Section: Efferent Thoracic Dum Neurons Can Be Divided In Subpopulatiomentioning
confidence: 94%
“…It has recently been reported that corollary discharges during singing inhibit the GI's responses to air-puff stimuli (Schöneich and Hedwig, 2015). However, some multimodal interneurons that respond to both auditory and air-puff stimuli have been identified in the cephalic and prothoracic ganglia (Gras et al, 1990;Schildberger, 1984a). It is possible that the cercal and auditory signals are combined in the cephalic and thoracic ganglia.…”
Section: Neural Basis Of Cross-modal Modulation In Escape Behaviormentioning
confidence: 99%
“…This seems feasible considering that specific octopaminergic neurones are activated by flight or flightinducing stimuli (Gras et al, 1990;Ramirez and Orchard, 1990;Duch et al, 1999; for review, see Bräunig and Pflüger, 2001) and that specific octopaminergic neurones invade all brain neuropiles (Bräunig, 1991;Hammer, 1993), including areas in which electrical stimulation elicits aggression (cf. Huber, 1955).…”
Section: General Conclusionmentioning
confidence: 99%